PENGARUH MODEL AKAD PEMBIAYAAN TERHADAP PROFITABILITAS BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) DI INDONESIA - Rizka Saputri; Memet Agustiar; Hayet Hayet; Abd. Mubaraq; Hesti Diah Ayuni (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
This study aims to analyze the effect of partnership-based financing sale-based financing, lease-based financing, and qardh financing on the profitability of Islamic Rural Banks (Bank Pembiayaan Rakyat Syariah/BPRS) in Indonesia, as measured by Return on Assets (ROA). This study employs a quantitative method with a descriptive approach using secondary data obtained from the Islamic Banking Statistic published by Financial Services Authority (Otoritas Jasa Keuangan/ OJK). The results indicate that partnership-based financing, sale-based financing, and qardh financing have a positive and significant effect on ROA, while lease-based financing has a negative but insignificant effect. These findings suggest that optimizing partnership-based, sale-based, and qardh financing can enhance the profitability of BPRS, whereas the management of lease-based financing still needs to be improved to provide a greater contribution to financial performance. Keywords : Partnership contract, Sale and Purchase Contract, lease Contract, Qardh Contract, ROA